Tumor grade and sex should influence the utilization of portal lymphadenectomy for early stage intrahepatic cholangiocarcinoma. Issue 4 (April 2019) - Martin, Sean P.; Ruff, Samantha; Diggs, Laurence P.; Drake, Justin; Ayabe, Reed I.; Brown, Zachary J.; Wach, Michael M.; Steinberg, Seth M.; Davis, Jeremy L.; Hernandez, Jonathan M.
Abstract: Background: Portal lymphadenectomy for intrahepatic cholangiocarcinoma (ICC) is encouraged for staging purposes, though it is under-utilized for clinically early-stage tumors. We sought to determine if any factor knowable prior to resection influences rates of portal lymph node metastases. Methods: The Surveillance, Epidemiology, and End Results (SEER) Program (1973–2014) database was queried to identify patients with T1/T2 ICC undergoing resection. Patients were stratified by lymph node (LN) status. Patients deemed LN negative required examination of six or more LNs (AJCC guidelines). Results: One-hundred and fifty-two patients were included in the analysis (LN negative: 38, LN positive: 114). Patients with LN negative cancers experienced prolonged overall survival as compared to patients with positive LNs (median 77 months vs 19 months, respectively p < 0.001). Twelve patients had well-differentiated tumors (G1), 92 patients had moderately-differentiated tumors (G2) and 58 patients had poorly-differentiated tumors (G3). Tumor grade (OR 3.9, CI 1.1–13.7, p = 0.031) and male sex (OR 2.6, CI 1.1–6.1, p = 0.022) were associated with positive LNs on multivariable logistic regression analysis. Conclusion: Intermediate/High grade and male sex are associated with high rates of lymph node metastasis for patients with early-stage ICC, which portends abbreviated overall survival.